2018
DOI: 10.1016/j.gfs.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from women's group-based programs to nutrition change in South Asia: A conceptual framework and literature review

Abstract: Improving the nutritional status of women and children in South Asia remains a high public health and development priority. Women's groups are emerging as platforms for delivering health- and nutrition-oriented programs and addressing gender and livelihoods challenges. We propose a framework outlining pathways through which women's group participation may facilitate improvements in nutrition. Evidence is summarized from 36 studies reporting on 24 nutritional indicators across infant and young child feeding (IY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
77
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 53 publications
(82 reference statements)
10
77
2
Order By: Relevance
“…This is likely due, in part, to participatory cooking demonstrations that frequently occur alongside counseling/coaching during group sessions and which have been shown to be effective for improving complementary feeding practices [34]. Our findings are consistent with a review of 36 studies that showed that women's groups focused on behaviour change are beneficial for improving child feeding practices in South Asia [13].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is likely due, in part, to participatory cooking demonstrations that frequently occur alongside counseling/coaching during group sessions and which have been shown to be effective for improving complementary feeding practices [34]. Our findings are consistent with a review of 36 studies that showed that women's groups focused on behaviour change are beneficial for improving child feeding practices in South Asia [13].…”
Section: Discussionsupporting
confidence: 84%
“…Pooled estimates from studies using both home visit and group platforms showed positive results for EIBF (OR: 2.13; 95% CI: 1.12, 4.05; n = 9), EBF (OR: 2.43; 95% CI: 1.70, 3.46; n = 12), and < 5 wasting (OR: 0.77; 95% CI: 0.67, 0.89; n = 4). Our findings underscore the importance of interpersonal community platforms for improving infant and young child feeding practices and children's nutritional status in LMICs.Nutrients 2020, 12, 440 2 of 16 due to limited knowledge surrounding how best to integrate nutrition-focused interventions into these routine activities at the country level [13].Emerging evidence indicates that advancements in nutrition require nutrition-sensitive programmes that enhance the coverage and effectiveness of direct nutrition interventions [14]. Cash transfers requiring compliance with specific health/nutrition behaviours are commonly used in social protection/safety net programmes in LMICs [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Group membership in nutrition education or mother‐to‐mother support groups is shown to have a positive relationship with maternal information and knowledge (Lutter et al, ; Nair et al, ; Singh et al, ). Group‐based approaches are increasingly seen as an important strategy to improve maternal and child nutrition outcomes through multiple social, economic and agricultural paths (Brody, De Hoop, Vojtkova, Warnock, & Dunbar, ; Kumar et al, ). Group membership through targeted nutrition programming and relevant behaviour change messages may improve IYCF outcomes (Kumar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, social participation can facilitate information and knowledge exchange, which can improve access to health resources and knowledge networks related to child nutrition, thus improving IYCF practices (Harpham, De Silva, Jones, & Garlick, ; Lin, ). Membership in groups, especially in those that include information on maternal and child nutrition, has shown significant positive association with improved IYCF practices in South Asia (Kumar et al, ; Sraboni, Malapit, Quisumbing, & Ahmed, ). Women with lower workload and greater household decision‐making control may have more opportunities to seek health services and information during pregnancy and after child birth to follow recommended IYCF practices (Carlson, Kordas, & Murray‐Kolb, ; Duong, Binns, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%